Improving the Performance of Electricity and Water and Sanitation Utilities in Sub-Saharan Africa - World Bank Group (World Bank, Washington, DC, 2017)
This paper is a synthesis of the findings of reports that look at the drivers of performance in energy and water utilities in Sub-Saharan Africa. This paper also provides other insights on issues that complement the findings of these reports. Additional data and evidence were harvested from the analysis of water and electricity utilities in all three reports, which enabled a broader perspective on the sector wide variables impacting performance, beyond internal variables for specific utilities. The two water studies provide guidance on how to provide good quality services to customers, including the poor. In contrast, because of data constraints, the energy study was limited to a narrower but deeper assessment of operational performance in Burkina Faso, Côte d’Ivoire, Kenya, Senegal, and Uganda. The reports fill a gap in the literature of the utilities’ performance in Sub-Saharan Africa and expand on the determinants for performance, identify the traditional and nontraditional mechanisms for reaching the poor, and highlight the critical elements for turning bad-performing utilities around. While the three background reports provide a significant step ahead (as they serve mainly as a mirror for performance assessment at the country and utility level), the reports also aimed at providing direction in the region for sector-wide improvement.